การพัฒนาประสิทธิภาพการจัดทำบัญชีครัวเรือนของเกษตรกร (THE DEVELOPMENT OF HOUSEHOLD ACCOUNTING EFFICIENCY OF FARMERS) - วิจิตรเสถียร สรียา (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2017)
การวิจัยนี้มีวัตถุประสงค์เพื่อสำรวจลักษณะองค์ความรู้ทางการบัญชีที่เกษตรกรทั้งกลุ่มที่สามารถจัดทำบัญชีได้และกลุ่มที่ทำไม่ได้ เพื่อหาสาเหตุที่เกษตรกรทั้งกลุ่มที่สามารถจัดทำบัญชีได้และกลุ่มที่ทำไม่ได้ยังคงต้องการความรู้ด้านการบัญชีเพิ่มเติมทั้งที่ได้รับการอบรมความรู้ไปแล้วและเพื่อเปรียบเทียบองค์ความรู้ที่เกษตรกรทั้งกลุ่มที่สามารถจัดทำบัญชีได้และทำไม่ได้ต้องการ เพื่อหาแนวทางในการพัฒนาประสิทธิภาพในการจัดทำบัญชีครัวเรือนของเกษตรกรต่อไป โดยกลุ่มตัวอย่างที่ใช้ในการวิจัยเป็นเกษตรกรที่เข้าร่วมโครงการเสริมสร้างภูมิปัญญาทางบัญชีแก่เกษตรกรไทย โดยกรมตรวจบัญชีสหกรณ์ ที่อยู่ในตำบลธารทอง อำเภอพาน จังหวัดเชียงราย ทั้งเกษตรกรที่สามารถบันทึกบัญชีได้แต่ต้องการความรู้เพิ่มเติม จำนวน 210 คน และเกษตรกรที่ไม่สามารถบันทึกบัญชีได้และต้องการความรู้เพิ่มเติม จำนวน 86 คน รวมตัวอย่างที่ใช้ในการวิจัยนี้ทั้งสิ้น 296 ตัวอย่าง จากการศึกษาลักษณะองค์ความรู้ทางการบัญชีครัวเรือนเปรียบเทียบกันระหว่างกลุ่มเกษตรกรที่สามารถจัดทำบัญชีครัวเรือนได้กับเกษตรกรที่ไม่สามารถจัดทำบัญชีครัวเรือนได้พบว่า ถึงแม้เกษตรกรกลุ่มหนึ่งจะไม่สามารถจัดทำบัญชีครัวเรือนได้ แต่เกษตรกรกลุ่มนี้มีความรู้และความเข้าใจเกี่ยวกับความหมายและความสำคัญของการจัดทำบัญชีครัวเรือน การแยกประเภทรายรับ-รายจ่าย รวมถึงรู้และเข้าใจวิธีการบันทึกบัญชีและเรื่องของการวางแผนและกำหนดเป้าหมาย ดีกว่าเกษตรกรที่มีความสามารถในการจัดทำบัญชีครัวเรือน ซึ่งสาเหตุของการที่เกษตรกรไม่สามารถจัดทำบัญชีได้นั้น คือ ปัญหาจากความสามารถในการอ่านออกเขียนได้ ระดับการศึกษา อายุ การไม่เห็นถึงความสำคัญในการจัดทำบัญชีครัวเรือน และไม่มีการฝึกปฏิบัติการจัดทำบัญชีหลังจากการเข้ารับการอบรมแล้ว ซึ่งทำให้เกษตรกรกลุ่มนี้มีความรู้ ความเข้าใจในเรื่องการสรุปยอดรายรับ-รายจ่าย และการวิเคราะห์เปรียบเทียบข้อมูลรายรับ-รายจ่าย น้อยกว่ากลุ่มเกษตรกรที่มีความสามารถในการจัดทำบัญชี การวิจัยยังพบว่า องค์ความรู้ที่กลุ่มเกษตรกรที่ไม่สามารถจัดทำบัญชีได้ต้องการมากที่สุด 3 อันดับแรกคือ การบันทึกรายรับ-รายจ่าย การแยกประเภทรายรับ-รายจ่าย และต้องการวิธีการสอนการจัดทำบัญชีที่ง่ายขึ้นส่วนองค์ความรู้ที่กลุ่มเกษตรกรที่สามารถจัดทำบัญชีได้ต้องการมากที่สุด 3 อันดับแรก คือ ความรู้ในเรื่องการคิดคำนวณต้นทุน การแยกประเภทรายรับ-รายจ่าย และการวางแผนและควบคุมทางการเงิน คำสำคัญ: บัญชีครัวเรือน เกษตรกร ประสิทธิภาพการจัดทำบัญชีครัวเรือน This is a study of whether the agricultural groups know how to create and handle the household account and to look for reasons why some of the agricultural groups can create a household account while the others cannot although all agricultural groups have been provided the knowledge of creating and handling a household account. The study compares the intellectual knowledge among agricultural groups who can create the household account but the result is not satisfactory. In addition, this study tries to find out the reason why the agricultural groups cannot create and handle their household account properly, including comparing the results among the groups who can and who cannot create the household account. This study is confined to an investigation of 296 farmers who attended the project of the Accounting Intellectual Reinforcement for Thai farmers by the Cooperative Auditing Department, located in Thanthong, Phan District, Chiang Rai. The samples are divided into 2 groups. The first group comprises 210 farmers who know how to create the household account and make a record, but want to study more about accounting/financial knowledge. The other group consists of 86 farmers who do not know how to create the household account and make a record but want to study more. With the study of the household account intellectual knowledge by comparing among the farmers who are able to create and handle the household account with the farmers who are not able to do so, it is found that some of the farmers/agricultural groups can handle the household account properly while some of the agricultural group cannot. This is due to their inability to read and to write, their educational levels, age and lack of understanding of the importance of the household account and balancing the income and expenses. They also do not practice managing the household account after training. For the group that can manage the household account properly, the farmers understand the concept and the importance of household account and they are able to categorize income and expenses. They also understand how to make a record of household account, make a plan and set their target. In addition, the study shows that the first three intellectual concepts that farmers (who cannot manage their household account) need to know the most are the way to record income and expenses, the differentiation of income and expenses, the easy and uncomplicated way for their household account learning. On the other hand, what the farmers who can manage their household account need to know are the knowledge of calculating the capital cost, the categorization of income and expenses and planning and financial control respectively. Keywords: Household Account, Farmer, Household Accounting Efficiency